Molecular-assisted analysis of indigenous chicken semen to increase rooster fertility in tropics - Jacob Alhassan Hamidu; Richard Tsekumah; Amina Iddrisu; Stepehn Gariba; Mitchell Agyei Opoku; Emmanuel Kafari; Kofi Appenteng; Patrick Nana Kyere (Academia Biology)
Male fertility impacts greatly on hatchability and chick quality. The study assessed semen and sperm quality characteristics of indigenous chicken breeds. Ten brown normal feathered (NF) birds and 10 brown naked neck (NN) birds selected over six generations were investigated for semen volume, concentration, viscosity, sperm viability, morphology, motility, and sperm DNA fragmentation to predict fertility. The results showed that the mean semen volume of NF males (0.399 ml) was higher compared to NN males (0.237 ml.) The sperm viability count through a trypan blue exclusion test in NF was lower (62.7%) compared to NN (67.0%). However, the sperm concentration in NN cocks (4.3 × 106 sperms/ml) was higher compared to NF birds (3.0 × 106 sperms/ml) (p < 0.05). The morphology of sperms indicated that the percentage of normal sperms in NF versus NN was 69% and 71%, while the percentage of abnormal sperms was 31% as against 29%. Although NN had a high normal-to-abnormal sperm ratio, a high amount of normal sperm was recorded in NF as compared to the NN. However, the sperm motility pattern indicated that the movement of sperm in NN males was better than NF birds. DNA fragments from NF chicken sperms were lighter in weight and ran faster through the gel matrix, indicating higher amount of DNA fragmentation than the NN chickens. The semen and sperm analysis indicates fertility differences resulting from males between the two breeds in hot temperature conditions with the NN showing higher potential for higher fertility than NF birds.